Eksistensi Jaminan Hak Tanggungan Sebagai Jaminan Cross Collateral - Sinaga, Roulinta Yesvery; Dyastuti, Risqi Mumpuni (KANJOLI Business Law Review, 2023)
The freedom to impose more than one mortgage as stated in Article 5 of the Mortgage Right Act is a gap in the misconception of guarantee execution. The existence of more than one debtor or more than one creditor but still on the same collateral motorcycle taxi requires a strict application of clauses in the agreement.The purpose of this study is to examine the existence of mortgage rights as cross-collateral guarantees. This research was carried out in a normative juridical manner, using library data as secondary data for the study of rules and norms in law. The conclusion obtained from this study is that the imposition of mortgage rights can be carried out through two series of activities, namely the granting of mortgage rights and registration of mortgage rights. The freedom to be burdened with more than one mortgage to guarantee more than one debt is waived by Article 5 UUHT. The history of recording more than one mortgage will be recorded on the Mortgage Certificate (SHT) with the mention of the first/second/third rank and so on. The execution of mortgage rights can be carried out by Article 20 UUHT, namely based on the execution parate in Article 6 UUHT, Based on the executorial title in Article 14 and voluntary sale by agreement of both parties Article 20 paragraph (2). Execution constraints are still encountered in practice, especially in the imposition of more than one mortgage. The meaning of the priority principle is a misconception of the appropriate agency. In order to minimize execution constraints, the use of the cross-collateral clause is a way for the application of the creditor prudence principle. The use of cross-collateral which is equipped with cross-default and confirmed in the collateral agreement for collateral registration is then carried out.